Fast and Facile Microwave Synthesis of Cubic CuFe2O4 Nanoparticles for Electrochemical CO2 Reduction. Issue 4 (6th April 2023) - Zander, Judith; Weiss, Morten; Marschall, Roland
Abstract : CO2 Reduction In article number 2200184, Roland Marschall, and co‐workers prepared CuFe2 O4 nanoparticles via microwave‐assisted aqueous sol‐gel synthesis all ready in one minute. Synthesis time and temperature can be used to tailor their performance in CO2 reduction to CO.